2000
DOI: 10.1111/j.1526-4610.2000.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Sumatriptan for the Range of Headaches in Migraine Sufferers: Results of the Spectrum Study

Abstract: Background.-Migraineurs experience a spectrum of headaches: migraine, migrainous, and episodic tensiontype as defined by the International Headache Society (IHS).Objective.-To evaluate the effectiveness of sumatriptan, 50-mg tablets, in treating the spectrum of headaches in IHS-diagnosed migraineurs.Design/Methods.-Migraineurs with severe disability (Headache Impact Questionnaire score 250 or greater) were enrolled in a randomized, double-blind, placebo-controlled, crossover study. Patients treated up to 10 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
129
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(132 citation statements)
references
References 27 publications
(43 reference statements)
2
129
1
Order By: Relevance
“…Investigating the use of analgesics is important if we are to understand and correctly treat patients with chronic daily headache. Evidence suggests that patients with combined migraine and TTH (mixed headache) may experience relief of both headache syndromes by treatment with triptans (19). A relatively low rate of patient satisfaction in the subgroup of mixed headache patients found in this study may suggest that these patients were wrongly classi ed, or that they received suboptimal treatment from the specialist.…”
Section: Discussioncontrasting
confidence: 43%
“…Investigating the use of analgesics is important if we are to understand and correctly treat patients with chronic daily headache. Evidence suggests that patients with combined migraine and TTH (mixed headache) may experience relief of both headache syndromes by treatment with triptans (19). A relatively low rate of patient satisfaction in the subgroup of mixed headache patients found in this study may suggest that these patients were wrongly classi ed, or that they received suboptimal treatment from the specialist.…”
Section: Discussioncontrasting
confidence: 43%
“…The present study demonstrated the efficacy of oral sumatriptan (100 mg) for the spectrum of migraine attacks in a population of patients self-reporting with menstrually related migraine. To support this, recent studies have shown that oral sumatriptan (50 mg) is an effective treatment for the spectrum of headaches reported by the general population of migraine sufferers [26].…”
Section: Discussionmentioning
confidence: 98%
“…Secondly, recent studies have demonstrated that severely affected migraine sufferers have multiple clinical presentations of their migraine attacks, from true migraine, through migrainous headache to tension-type headache. However, this entire spectrum of headache may be a manifestation of the migraine process [26].…”
Section: Discussionmentioning
confidence: 99%
“…Using post-hoc analysis, Cady and colleagues [20] studied both the Spectrum study [21,23] and the M09 study authored by Pfaffenrath et al [22] to examine the results for patients who violated the clinical protocol and treated acute attacks with either sumatriptan or placebo at mild level pain, rather than waiting for moderate to severe level pain. Both studies offered placebo-controlled, albeit non-randomized groups of patients to compare the outcomes of treating mild versus moderate to severe level pain for sustained pain-free response [20][21][22][23].…”
Section: Stratified Carementioning
confidence: 99%
“…Both studies offered placebo-controlled, albeit non-randomized groups of patients to compare the outcomes of treating mild versus moderate to severe level pain for sustained pain-free response [20][21][22][23].…”
Section: Stratified Carementioning
confidence: 99%